HUBUNGAN BERAT BADAN DAN PANJANG TUNGKAI TERHADAP KECEPATAN LARI SPRINT 100 METER - erfi utami (Journal of Physical Education and Sport Science, 2022)
Body weight is very influential on a person's movement activity, because if the body is overweight or obese it will burden the movement that occurs. The ability to run 100 meters requires maximum speed to reach the finish. A person's weight will greatly affect the ability to run optimally, because the heavier the load carried by a runner will certainly hinder the speed of his running. The limbs of each individual have different sizes so that it affects the difference in the running speed of each individual. The longer a person's legs allow a person to walk longer and more efficiently in the distance being contested. The data obtained were analyzed for hypothesis testing, namely the t-test. The results of the final data analysis concluded that: (1) There is a relationship between weight on the speed of the 100 meter sprint of 0.332. (2) There is a relationship between leg length on the 100 meter sprint running speed of 3,552. (3) between body weight and leg length, which has more influence on the 100 meter sprint running speed is body weight, which is 0.744